Profitability, Leverage, Company Size and Institutional Ownership with The Gender Diversification Moderation of The Board of Directors on Tax Avoidance - Siregar, Amelia Oktrivina; Masri, Indah; Susilawati, Susilawati; Erlangga, Aldy Putra (Fakultas Pendidikan Ekonomi dan Bisnis, 2020)
The purpose of this research is to examine whether the influence of profitability, leverage, company size and institutional ownership with moderation of board gender diversification on tax avoidance in the automotive sector manufacturing companies in the 2012-2019 period. The sample in this study consisted of four companies that entered consistently during the research year. The period used in this research is eight years, from 2012 until 2019. The analysis data technique is panel data regression. The method used is purposive sampling method. The results of this research indicate that partially the profitability variable has a negative effect on tax avoidance. Leverage has a negative effect on tax avoidance. Company size has a negative effect on tax avoidance. Institutional ownership has a negative effect on tax avoidance. Gender cannot moderate the effect of Profitability on Tax Avoidance. Gender can moderate the effect of Leverage on Tax Avoidance. Gender cannot moderate the effect of Company Size on Tax Avoidance. Gender cannot moderate the effect of Institutional Ownership on Tax Avoidance. While simultaneous testing shows that the variable profitability, leverage, company size, institutional ownership and gender affect tax avoidance.